2017
DOI: 10.5152/etd.2017.17023
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Foot Care in Diabetic Inpatients: A Descriptive Cross-Sectional Study

Abstract: Objective: To determine whether diabetic patients have adequate information regarding foot care. Materials and Methods:We evaluated history of diabetic foot ulcer (DFU) and data on self-foot care practices collected through face-to-face interviews from 64 diabetic inpatients in a university hospital. Foot care practices were scored based on 20 questions. Questions under the categories of "beware of risky behavior," "foot and nail care," and "elaborate on footwear" were grouped, and the practice subscores and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…In contrast, the practice of self-foot care among patients with diabetes in Tanzania was low, although they were aware of the risk of developing diabetic foot ulcers (Chiwanga & Njelekela, 2015). This seems to be in line with a study by Dündar & Akıncı (2017), where they reported that patients who received education on self-foot care have good practice as compared to the patients who did not receive an education. It could be expected that knowledge and information could influence practice.…”
Section: Table 5: Association Between Knowledge and Practice Of Self-...supporting
confidence: 72%
“…In contrast, the practice of self-foot care among patients with diabetes in Tanzania was low, although they were aware of the risk of developing diabetic foot ulcers (Chiwanga & Njelekela, 2015). This seems to be in line with a study by Dündar & Akıncı (2017), where they reported that patients who received education on self-foot care have good practice as compared to the patients who did not receive an education. It could be expected that knowledge and information could influence practice.…”
Section: Table 5: Association Between Knowledge and Practice Of Self-...supporting
confidence: 72%
“…This questionnaire was designed by Dündar and Akinci (2017) and included 20 items with yes (score 1) and no (score zero) answers [17]. A higher score indicates better foot care performance.…”
Section: Measures and Data Collection The Practice Of Foot Care Quest...mentioning
confidence: 99%
“…26,32 To minimise complications, especially those that may lead to an amputation, diabetic patients should learn proper foot care. 30,33,34 Studies have shown that the development of DFUs is influenced by several factors such as age, educational background, weight, DM type, foot care hygiene or practices, and the existence of complex nerves disorders. 15,35,36 However, even with measures taken to prevent complications, which were also found to be cost-effective, DFUs persist, becoming a challenge for the patient and the health care system.…”
Section: Introductionmentioning
confidence: 99%